ANALISIS NILAI EKONOMI TAMAN DHARMA WANITA KOTA PEKANBARU (METODE CONTINGENT VALUATION) - Silvia Muldani; Hainim Kadir; Toti Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to determine the overall assessment of visitors to the Dharma Wanita garden of Pekanbaru City and also to find out, as well as to determine the demand for economical value or level visits with Contingent Valuation method. Total population used as samples in this study were 100 people. The method used in this study is accidental sampling. The analytical method used in this research is descriptive method using Valuatian Contingent approach. From the results of this study concluded that the general assessment visitors against Dharma Wanita garden of Pekanbaru City is pretty good. It can be found that most of the visitor answers by 37%. Majority of visitors came from the city of Pekanbaru. Economical value and the level of demand or visitation level of Dharma Wanita garden of Pekanbaru city with Contingent Valuation Method, that can be found from total income of WTP’s visitors to the City of Rp.383.750 per day and the amount will increase on holidays.Keywords: Economic Values and Contingent Valuation Methods